2011
DOI: 10.1039/c0cc05749e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of an ultrathin carbon shell coating a silver core for shell-isolated nanoparticle-enhanced Raman spectroscopy

Abstract: A well-designed type of ultrathin carbon shell coating a silver core was prepared for the first time through an alternate adsorption and carbonization method. The obtained ultrathin carbon shell shows prominent advantages, including sufficient uniformity, better chemical stability than silica or alumina, biocompatibility, being free of pin-holes and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The technique, termed shell-isolated nanoparticle-enhanced Raman spectroscopy, or SHINERS, has dramatically expanded the practical application of SERS, enabling measurements on effectively any substrate due to the minimal interference of the 'SHIN' resonators [82][83][84]. Procedures to synthesise SHINs are now well-documented [85], typical particles comprising a 55-120 nm spherical gold or silver core [82,86,87] [92], graphene [93,94] and other carbon materials [95,96]. Example core-shell particles are depicted in Figure 5 The substrate generality of SHINERS has greatly benefitted electrochemical Raman spectroscopy and an impressive range of native electrode substrates have been investigated including Ag [97,98], Au [99][100][101][102][103][104], Pt [99,102], Pd [102], Rh [105], Ni alloys [106,107], Cu [108] and glassy carbon (GC) [102].…”
Section: Ec-shinersmentioning
confidence: 99%
“…The technique, termed shell-isolated nanoparticle-enhanced Raman spectroscopy, or SHINERS, has dramatically expanded the practical application of SERS, enabling measurements on effectively any substrate due to the minimal interference of the 'SHIN' resonators [82][83][84]. Procedures to synthesise SHINs are now well-documented [85], typical particles comprising a 55-120 nm spherical gold or silver core [82,86,87] [92], graphene [93,94] and other carbon materials [95,96]. Example core-shell particles are depicted in Figure 5 The substrate generality of SHINERS has greatly benefitted electrochemical Raman spectroscopy and an impressive range of native electrode substrates have been investigated including Ag [97,98], Au [99][100][101][102][103][104], Pt [99,102], Pd [102], Rh [105], Ni alloys [106,107], Cu [108] and glassy carbon (GC) [102].…”
Section: Ec-shinersmentioning
confidence: 99%
“…To form carbon shells, Yang et al deposited p-mercaptobenzoic acid on the surface of silver nanoparticles and then carbonized the deposited organic layer in a concentrated solution of sulphuric acid. TEM analysis of the nanostructures obtained showed that, after this procedure, the silver cores are covered by a carbon layer with a thickness of about 2 nm (Yang et al, 2011). SHINERS nanoresonators protected by a layer of polydopamine have been synthesized by Ye et al (2017).…”
Section: Formation Of the Protective Layermentioning
confidence: 99%
“…Hence, considerable efforts have been focused on the development of carbon or graphene SHINs. Yang et al have prepared ultrathin carbon‐shell‐isolated Ag nanoparticles by carbonization ( Figure a) . They modified 4‐mercaptobenzoic acid molecules on the Ag nanoparticle surface via the formation of an Ag–S bond through the adsorption of cetyltrimethylammonium bromide (CTAB) on Ag nanoparticles via electrostatic interaction.…”
Section: Synthesis Of Various Shell‐isolated Nanoparticlesmentioning
confidence: 99%
“…f) Carbon dot (CD)‐coated Au nanoparticles. (a) Reproduced with permission . Copyright 2011, the Royal Society of Chemistry.…”
Section: Synthesis Of Various Shell‐isolated Nanoparticlesmentioning
confidence: 99%